Contemporary reception of gnosis in Poland: Jerzy Prokopiuk and the quest for spirituality - Jocz, Artur (Człowiek i Społeczeństwo, 2016)
While discussing gnosis in contemporary Polish culture, it is impossible to overlook the figure of Jerzy Prokopiuk (born 1931). But Prokopiuk’s body of work should not be judged solely on the merit of his prolific publishing and popularising activity, as one should also take into consideration his spiritual, intellectual and gnostic explorations, as well as how they contributed to the historical reception of gnostic ideas in Poland. This is why this paper will seek to present Prokopiuk’s views on the essence of God, the nature of the world, and the human phenomenon.